2005
DOI: 10.1038/sj.bjc.6602469
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly vinorelbine and 24-h infusion of high-dose 5-fluorouracil plus leucovorin as first-line treatment of advanced breast cancer

Abstract: We prospectively investigated the efficacy and safety of combining weekly vinorelbine (VNB) with weekly 24-h infusion of high-dose 5-fluorouracil (5-FU) and leucovorin (LV) in the treatment of patients with advanced breast cancer (ABC). Vinorelbine 25 mg m À2 30-min intravenous infusion, and high-dose 5-FU 2600 mg m À2 plus LV 300 mg m À2 24-h intravenous infusion (HDFL regimen) were given on days 1 and 8 every 3 weeks. Between June 1999 and April 2003, 40 patients with histologically confirmed recurrent or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One study of metastatic breast cancer from Chang Gung Memorial Hospital, Taiwan showed that the 1-year survival rate was 70.5%, and the 2-year survival rate was 32.9% [44]. Another study from the National Taiwan University Hospital showed that the 1-year survival rate was 80.0%, and the 2-year survival rate was 50.0% [86].…”
Section: Discussionmentioning
confidence: 96%
“…One study of metastatic breast cancer from Chang Gung Memorial Hospital, Taiwan showed that the 1-year survival rate was 70.5%, and the 2-year survival rate was 32.9% [44]. Another study from the National Taiwan University Hospital showed that the 1-year survival rate was 80.0%, and the 2-year survival rate was 50.0% [86].…”
Section: Discussionmentioning
confidence: 96%
“…In first-line setting Cetuximab has been evaluated in combination with different regimens of chemotherapy, such as 5FU, folinic acid, irinotecan (iri) (FOLFIRI) [20], docetaxel/cisplatin (cis) [21], FOLFOX [22], (capecitabine (cape), oxaliplatin (ox) (XELOX) [23], weekly iri, infusional 5FU, leucovorin (FUFIRI) [24], continuous infusion high dose 5FU/leucovorin /cis [25], cape/cis [26], and ox/iri [27]. …”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…In view of its mild toxicity profile, VNB can be easily combined with many other drugs like taxanes, anthracyclines, gemcitabine, 5-fluorouracil, platinum compounds and capecitabine. In comparative studies, combined strategy is not always superior to the optimal sequential therapy and is often more toxic (Mano 2006;Yeh et al 2005;Berruti et al 2000Berruti et al , 2005Campone et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Objective response rate is nearly 45% in first line treatment and 20-30% in previously treated patients. In combination with other chemotherapy agents the most employed schedule was VNB 25 mg/sqm on days 1 and 8 every 3 weeks (Mano 2006;Yeh et al 2005). In view of its mild toxicity profile, VNB can be easily combined with many other drugs like taxanes, anthracyclines, gemcitabine, 5-fluorouracil, platinum compounds and capecitabine.…”
Section: Introductionmentioning
confidence: 99%